KEANEKARAGAMAN ANGGREK DI KAWASAN CAGAR ALAM LEMBAH ANAI KABUPATEN TANAH DATARSUMATERA BARAT - Febriani, Mira; Nursyahra, Nursyahra; Des, Des (STKIP PGRI Sumbar, 2013)
ABSTRACT Orchids live an cool and humid habitat in tropical forest so that its biodiversity is quite high in that area. Lembah Anai Nature Reservation is one of Nature Reservation which is located in West Sumatera. There is still few information or documentation reports and images that reveal the biodiversity of Orchids in Lembah Anai Nature Reservation. The aims of this research is know and describe the biodiversity of Orchids in Lembah Anai Nature Reservation, Tanah Datar regency of West Sumatera. The research is conducted from March to July 2013 by using direct survey. The research is done in the north side of Lembah Anai Nature Reservation along forest patrol path. Then, the specimen isidentified in the Botany laboratory of Padang State University and Herbarium Andalas (ANDA), Padang.From this research, it is found that there are 21 species of orchids from16 genus, which consist of epiphytic Orchids such as Agrostophyllum glumaceum Hook.f., Agrostophyllum sp., Appendicula sp., Bulbophyllum membranaceum Teijsm & Binn., B. uniflorum (Bl.) Hassk., Bulbophyllum sp., Coelogyne rochusseni de Vriese, Dendrochilum cf.simile Bl., Dendrobium crumenatum Sw., Dendrobium sp., Eria sp., Bulbophyllum condylobulbon Rchb.f., Pholidota imbricata (Roxb.) Lindl., P. ventricosa (Bl.) Rchb.f., Pomatocalpa latifolia (Lindl.) J.J. Sm., Thrixspermum sp., and 5 species of teresterial Orchids such as Apostasia nuda R.Br., Calanthe sp., Macodes petola (Bl.) Lindl., Plocoglottis plicata (Roxb.) Ormerod., Tainia sp.. Based on this finding, it is suggested that there will be a further research of inventory of the biodiversity Orchids on the south side of Lembah Anai Nature Reservation.